What do we know about pseudodementia? - Sara Ramos; Salomé Mouta; Isabel Fonseca Vaz; Miguel Pires; Diana Figueiredo (General Psychiatry, 2023)
Depression and dementia can lead to generalised cognitive and memory dysfunction. Thus, differentiating these disorders is important and challenging. Pseudodementia is a term used clinically to describe symptoms that resemble dementia but are caused by other conditions (most frequently depression), rather than being recognised as an official diagnosis. Pseudodementia is characterised by a cognitive impairment that mimics dementia but which does not have its origin in neurological degeneration, deriving instead from functional psychiatric conditions. This condition is more commonly observed in older adults (particularly those over the age of 50 or 60 years), and its risk factors overlap with those for depression. Pseudodementia is essentially characterised by deficits in memory, executive function and speech and, therefore, can easily be confused with dementia, although there are aspects that allow its differentiation. Diagnosing pseudodementia can be difficult, especially as there is significant overlap between its symptoms and those of other conditions. However, it is important to recognise characteristic aspects of this disorder, as its correct identification is essential for proper treatment.